"Groupy" Allies Are More Beneficial While "Groupy" Enemies Are More Harmful. Issue 8 (November 2018) - Dang, Jianning; Liu, Li; Ren, Deyun; Gu, Zibei
Previous research about group perception in terms of warmth and competence focused on the effects of social structural factors but overlooked the role of the fundamental group characteristic (i.e., entitativity or groupiness). Three studies were conducted to examine people's perception of high/low entitativity groups under various functional relations. In Study 1, we experimentally created the target group (i.e., Group X) and manipulated entitativity and functional relation. In Studies 2 and 3, we chose a real group (i.e., Uyghurs) as the target group and measured cues to entitativity (Study 2) or entitativity itself (Study 3) and interethnic relations. In all studies, participants rated the target group on warmth and competence dimensions. The results suggested that, under cooperative functional relation, the group with higher entitativity was perceived as more competent and warmer, thereby more beneficial. Conversely, when the functional relation was conflictive, the group with higher entitativity was perceived as more competent but colder, and thus more harmful.